INFLUENTIAL FACTORS IN CHOOSING HIGHER EDUCATION INSTITUTION: A CASE STUDY OF A PRIVATE UNIVERSITY IN SURABAYA - Adelina Proboyo; Ricky Soedarsono (Institute of Research and Community Outreach - Petra Christian University, 2015)
Nowadays, tertiary education has taken more important role for Indonesian people. The growing number of tertiary education enrollment rate accompanied by the increasing number of higher education insitutions in Indonesia show that there is opportunity as well as threat for higher education insitutions in Indonesia. The purpose of this research is to know what factors influence the high school students in choosing their higher education institution. Specifically, this research wants to help one of the best private universities in Surabaya to improve its competitiveness compared to other higher education institutions. The respondents of the research are 426 students from several high schools in Surabaya. The analysis is done using descriptive statistics to find out which factors are the most significant ones. From the research, it is found out that the students’ interest, the ability to follow the courses, and the parents’ advice are the top three significant factors that influence the high school students in choosing their higher education institution. For the attributes of the institution, the reputation and the values of the institution as well as the success of its alumni are the top three factors that influence the decision in choosing the higher education institution.